Kajian Hukum terhadap Tindak Pidana Peredaran Rokok Ilegal di Provinsi Lampung - M Farhan Nurfikri Z; Diah Gustiniati Maulani; Fristia Berdian Tamza (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effectiveness of law enforcement against the distribution of illegal cigarettes in Lampung Province, identify the main obstacles, and provide strategic recommendations. The findings reveal that law enforcement in this region remains suboptimal due to weak inter-agency coordination, limited human resources and facilities, and the complexity of offenders' modus operandi. Offenders often exploit administrative sanctions, which fail to provide a deterrent effect, allowing the circulation of illegal cigarettes to persist. The study recommends strengthening the application of criminal sanctions, enhancing coordination through inter-agency data integration, utilizing digital-based monitoring technology, and conducting continuous public education. Implementing these measures is expected to improve law enforcement effectiveness, reduce the circulation of illegal cigarettes, and positively impact state revenue and public health protection.